Eksplorasi Berpikir Aljabar Siswa Kelas 5 Dalam Menyelesaikan Soal Pemodelan - Kusuma Ardi, Sinta Devi; Masduki, Masduki (Jurnal Tadris Matematika, 2023)
Algebraic thinking is important for developing students' mathematical generalization abilities, and identifying patterns, shapes, and symbols. This study uses a qualitative descriptive approach that aims to describe the profile of students' algebraic thinking in solving modeling problems. The subjects of this study were 158 fifth-grade students in two private schools in Surakarta, Central Java. The data collection instrument used was six test questions related to the modeling component adopted from Ralston. Prior to use, the instrument was validated by 3 elementary school mathematics learning experts and tested on 10 students who were not the subject of the study. Based on the test results, there were 12 students who scored in the high category. This study focuses on analyzing the algebraic thinking profile of students with high categories. The results showed that high-category subjects were able to demonstrate understanding related to modeling indicators in algebraic thinking, namely understanding the meaning of the equal sign (=) as an equivalence relationship, using variables to solve problems in the form of equations, and understanding the relationships between arithmetic operations. However, a small number of subjects still experience calculation errors and understanding errors in algebraic operations. Hence, it can be concluded that subjects with high categories are able to demonstrate algebraic thinking skills in the modeling component